Effect of Processing Methods on Antioxidant Activity, Phenol and Flavonoid Content of Urtica kioviensis Leaves - Jaradat, Nidal; Ali, Iyad; Zaid, Abdel; Abualhasan, Murad (Jordan Journal of Pharmaceutical Sciences, 2017)
The cooking method may affect antioxidant capacity and total phenol and flavonoid content in many fruits and vegetables. These effects may cause degradation of anti-oxidant compounds, formation of new products or destruction of active metabolites. The aim of this study is to measure the antioxidant activity, total phenol and flavonoid contents of fresh Urtica kioviensis (U. kioviensis) leaves after being subjected to different cooking method. Antioxidant activity was assayed by using 2, 2-diphenyl-1-picryl-hydrazyl-hydrate, flavonoid content was determined by using Rutin reference standard method, and the total phenol content was determined by Folin-Ciocalteu method. Fresh U. kioviensis showed to possess the highest antioxidant capacity (IC50 value 19.95±0.21mg/ml) and the highest content of phenol (78.27±0.16mg GA/g) and flavonoid (43.3±0.00mg RU/g), followed by shade-dried extracts (70.19±0.22mg GA/g for phenol and 43.3±0.21mg RU/g for flavonoid). While the oven dried extracts and boiled possessed lower antioxidant capacity (IC50 value 28.18±0.18mg/ml and IC50 value 31.62±0.11mg/ml, respectively) and reduced phenolic (42.2±0.12 and 41.13±0.13mg GA/g, respectively) and flavonoid contents (15.6±24mg RU/g extract and 7.2±0.24mg RU/g extract, respectively). Fresh and shade dried U. kioviensis leaves have high antioxidant activity and are rich in phenol and flavonoid. Boiled or roasted leaves did not cause complete loss of their nutritional values. The fresh and shade dried U. kioviensis leaves remained preferred over boiled or oven-dried extracts as a nutrient and for preparing nutraceutical, cosmeceuticals and pharmaceutical supplements.